Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/ecin.12418
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Risk and Time‐varying Correlation Between Equity and Currency Returns

Abstract: Using data on twenty major OECD countries over time, this paper documents a new evidence on real equity and real currency prices: higher real returns in the home equity market relative to foreign counterparts are generally associated with real home currency depreciation at a monthly frequency, but this negative correlation breaks down or even reverses during times of relatively higher aggregate economic uncertainty or volatility. This paper also proposes one plausible explanation for this time-varying correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…In another related work, Pástor and Stambaugh (2003) also found that their liquidity measure sharply dropped in times of severe financial distress. In fact, in a recent study, examining the time-varying correlations between equity and currency returns, Jung (2017) argue that idiosyncratic volatility driven by the volatility in market liquidity acts as a channel that drives the time-variation in currency-equity correlations.All this evidence raises a question as to whether liquidity could possibly serve as the underlying factor, drivingthe time-variation incorrelations and/or amplifying the effect of volatility on correlations among asset classses, particularly in times of financial distress. This paper examines the effect of liquidity on the time-variation in the correlations among three major asset classes, particularly stocks, corporate bonds and commodities.…”
Section: Introductionmentioning
confidence: 99%
“…In another related work, Pástor and Stambaugh (2003) also found that their liquidity measure sharply dropped in times of severe financial distress. In fact, in a recent study, examining the time-varying correlations between equity and currency returns, Jung (2017) argue that idiosyncratic volatility driven by the volatility in market liquidity acts as a channel that drives the time-variation in currency-equity correlations.All this evidence raises a question as to whether liquidity could possibly serve as the underlying factor, drivingthe time-variation incorrelations and/or amplifying the effect of volatility on correlations among asset classses, particularly in times of financial distress. This paper examines the effect of liquidity on the time-variation in the correlations among three major asset classes, particularly stocks, corporate bonds and commodities.…”
Section: Introductionmentioning
confidence: 99%